Cinta: Objek dan Puisi (Konsep Cinta Erich Fromm dalam Puisi-puisi Karya W.S Rendra) - Adhea Tsabitah Sulistiyo; Syihabuddin Syihabuddin (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Love can be used as an answer to the question of human existence. So many philosophers from the west and east offer concepts about love, Erich Fromm is one of them who considers that love is an art. The purpose of this study is to classify five objects of love from Erich Fromm's thoughts in poems by W.S Rendra. Poetry was chosen as the object of research because poetry can be used as a means for someone to express love. This research method is a literature study as well as a literature review. The results of this study are five titles of poems that represent the five objects of love. First, object of brotherly love entitled "Aku Mendengar Suara" because this poem contains Rendra who loves his oppressed brothers. The object of maternal love titled "Ibunda" contains a mother's love that is like the earth that provides its fertility for her children to grow and sacrifices everything a mother has for her children, truly loving even though she does not get anything from the child. The object of erotic love with the title "Barangkali Karena Bulan" is about exclusive love to one person, namely the poet's love for a woman. Self-love with the poem titled "Orang Biasa" contains Rendra's love for himself. Last, the object of God's love titled "Tuhan, Aku Cinta Padamu" is about Rendra's desire to return to Him and achieve unification between the servant and his God.